PENGARUH MODEL PEMBELAJARAN PBL TERHADAP HASIL BELAJAR SISWA KELAS IX.11 DI MAN 2 KOTA SUKABUMI PADA MATA PELAJARAN FIQIH: The Transformation of Fiqh Learning Based on Problem-Based Learning to Strengthen Students' Cognitive, Affective, and Psychomotor Domains - Zaki, Muhammad; Nurdiana, Putri; Agustina, Risa; Premitha, Septy (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
The quality of Fiqh instruction at the Madrasah Aliyah level continues to face challenges, particularly in fostering student engagement and deep conceptual understanding of normative-reflective content. This study aims to evaluate the effectiveness of the Problem-Based Learning (PBL) model in improving student learning outcomes on the topic of "Pillars and Conditions of Marriage" at MAN 2 Kota Sukabumi. Employing a quantitative approach with a Classroom Action Research (CAR) design, the study was conducted in two cycles. Data were collected through formative tests, classroom observations, and student motivation questionnaires, and analyzed using both descriptive quantitative and qualitative methods. The findings reveal an increase in students’ average scores from 69.30 in the first cycle to 75.77 in the second cycle, with mastery learning rising from 59% to 94%. Additionally, affective and psychomotor indicators showed substantial improvement. These results indicate that PBL is effective in fostering active student engagement and enhancing contextual understanding in Fiqh learning. The practical implication suggests the broader adoption of PBL in religious education to develop students’ holistic 21st-century competencies.